Pressure effect on the spin-dependent electronic structure of Au intercalated h-BN/graphene/h-BN. (28th October 2016) - Xia, Youzhi; Li, Zhongyao
Abstract: The spin-dependent electronic structures of Au intercalated hexagonal-BN/graphene/hexagonal-BN under pressure or electric field are examined on the basis of density-functional theory. Two kinds of doping concentrations are considered: one-monolayer Au doping and 1/4-monolayer Au doping. In one-monolayer Au doped structure, the large band gap of graphene is mainly induced by the B–C interaction, while the large spin–orbit effect is from the C–Au interaction. Both the band gap and the spin–orbit splitting can be modulated by pressure. In the 1/4-monolayer Au doped structure, the conduction band around the Γ point is in the band gap of graphene with a Rashba constant of 0.12 eVÅ/ ħ . The Rashba effect can also be modulated by pressure and electric field. Our study provides a possible method to manipulate the spin-dependent electronic structure of graphene by proximity effect and extract the large spin–orbit effect of Au atoms.